Peningkatan Mutu Madrasah: Pendekatan Struktural, Kultural, dan Manajerial - SUHARDI Hardi (Universitas Muhammadiyah Tangerang, 2023)
Madrasah are formal educational institutions with Islamic characteristics that must continue to improve their quality. We should be grateful that in the last twenty years many superior madrasas have started to emerge, but in general these are state madrasah which account for approximately 5% of the total number of existing madrasah. anti-private madrasas, which account for approximately 95%, must continue to be advocated to improve their quality. There are at least three approaches that can be taken to encourage madrasah to become superior educational institutions, namely structural, cultural, and managerial approaches. This paper will explain how these three approaches can be developed to improve the quality of madrasah education.